A Study on Incidence of Inguinal Hernia in Relation to BMI - Sidra Riaz, Naveed Ali Khan, Abdul Khalique, Raazia Ramzan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Inguinal Hernias (IH) are the most common hernia of abdominal wall. These hernias affect both males and females. There are many factors that are linked with the increased risk of developing these hernias. Obesity is believed to be one of them. However, with current epidemiological advances, increased body mass index (BMI) has proven to have fewer incidences of inguinal hernias. Objective: The aim of this study is to determine the relationship of inguinal hernia both unilateral and bilateral with body mass index (BMI) Study Design: This is a cross-sectional study. Methodology: This study was conducted in the department of General Surgery Unit 2 of Dow University Hospital, Karachi, Pakistan. A total of 60 patients were included in this study using non probability convenient sampling which was conducted from January of 2022 till December of 2022. Results: A total of 60 patients who were clinically diagnosed with inguinal hernia were enrolled in our study. Their mean age was 39.25 ± 14.18 years, mean height was 170.55 ± 5.51 cm and mean weight was 67.28 ± 8.64 kg. Their average BMI was 23.10 ± 2.55 kg/m2. 56 (93.3%) of the participants were males and 4 (6.7%) were females. Only 1 (1.7%) patient with inguinal hernia was underweight, 48 (80%) patients were normal weighted, 10 (16.7%) patients were overweight and 1 (1.7%) patient was obese. Conclusion: According to the research that we conducted, most patients who underwent surgical hernia repair of either right, left or bilateral sides had normal BMI. Keywords: Inguinal Hernia, Body Mass Index (BMI)